Sur le modèle du labyrinthe, lorsque la littérature privilégie le jeu - D’humières, Catherine (Amaltea. Revista de Mitocrítica, 2009)
When we try to study how the myth of the labyrinth is being used in today’s litterature, we are striken by the extreme variety of the ways it has inspired. Indeed the pattern of the maze, always changeable and undefined, seems to trigger creativity. Deprived from the start of precise outlines, the labyrinth is a source of inspiration for all kind of fantasies, and proves to be favorable to a mixture of ways. Besides, it seems that time has enabled to create and strighten narrow links between labyrinth and fancy, and it is always fascinating to contemple the ways that may have played a part in the development of this creative fantasy. Through a few contemporary books, this article studies the link that some writers have tried to set up between labyrinth, game and writing itself, proving, it need be, the extreme vitality of a myth able to suit everyone’s fantasy, purposes or words, and to reflect, at the same time, the depth of the metaphysical interrogations present in the human mind.